A STUDY OF DEIXIS USED IN MICHAEL HEART’S SONGS LYRIC ENTITLED “WE WILL NOT GO DOWN AND “WHAT ABOUT US” - PUTRI, DIAN SYLVIANA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Pragmatics, Deixis, Michael Heart, Song, and Lyric.Communication has definition as the process of obtaining information or expressing  thought and feelings. Going by this definition, it is obvious that human beings are naturally communicators. Language is used to express inner thoughts, emotions, and  interactions  in  both spoken and written communication. Spoken means the process of expressing ideas and feelings or giving information is done orally. n understanding  a language, it is related to pragmatics  study. Pragmatics is a study on the language  expression in communicative  situation  to  get  some  meanings from the speakers. Therefore, pragmatics has a role in getting meanings. Pragmatics is concerned  with  the study of meaning as communicated by  a speaker (or writer) and interpreted by a listener (or reader). It has consequently more to do with the analysis of what people  mean  by  their  utterances  than  what the  words ofphrases in those utterances  might  mean  by  themselves.  Pragmatics  is  the  study  of speaker meaning, the study of contextual meaning, the study of how gets communicated than is said and the study of the expression of relative distance (Yule, 1996, p.3). One of the important elements in a laguange is deixis. Yule (1996, p.9) states that deixis is technical term for one of the most basic things that deal with utterance. Deixis is an utterance that has no sharp meaning. It can cause ambiguity in conversation.The writer used qualitative research and content analysis in order to answer the research problems. In this research, the writer classifies the deixis based on the classification made by Yule (1996). The writer also analyzes the interpretation of each deixis.  The data of this research on the lyrics of Micheal Heart song in a whole containing deixis. In data collection, the writer downloaded the songs and the lyrics, selected the utterances that contain deixis, and made a list of the utterances containing deixis terms.Total deixis is found in the lyrics of this amounted to 53 deixis, they are 41 person deixis, 4 spatial deixis and 8 temporal deixis in this lyric. Person deixis is the dominant type of deixis which is used in lyric “We Will Not Go Down” and “What About Us”. The writer limited the object since she just analyzed of whole the lyric so, the next researcher should analyze other song.The writer analyze especially type of deixis and the interpretation, the further researcher should chose another source of data to get the differences between analyzing deixis in a song and other sources, so it could have more data and information how deixis study is applied in many cases.